Arbuscular Mycorrhizal Fungi and NPK Fertilizer Enhance Growth and Yield of Bird’s Eye Chili: Peran Fungi Mikoriza Arbuskular dan Pupuk NPK dalam Meningkatkan Pertumbuhan dan Hasil Cabai Rawit - Mahmudi; Iwan Sasli (Universitas Widya Gama Mahakam, 2025)
The application of arbuscular mycorrhizal fungi can enhance the fertility of peat soils and reduce the requirement for NPK fertilization on the plat. The study aimed to evaluate the role of AMF in improving the growth and yield of bird’s eye chili and in supporting NPK fertilizer efficiency on peat soil. The experiment was conducted in Pontianak City, West Kalimantan, from July to November 2024, using a factorial completely randomized design. The first factor consisted of three levels of AMF application without AMF, AMF sourced from pineapple vegetation, and AMF sourced from weed vegetation. The second factor consisted of four levels of NPK fertilizer dosage 100% recommended NPK, 75% recommended NPK, 50% recommended NPK, and 25% recommended NPK. The results showed that the application of AMF significantly improved the growth and yield of bird’s eye chili on peat soil and enhanced the efficiency of NPK fertilization. The interaction between AMF and NPK dosages indicated that plants inoculated with AMF, particularly AMF from pineapple vegetation, exhibited greater plant height, higher plant dry weight, earlier flowering, and higher fruit weight per plant compared to plants without AMF across all fertilizer levels. The most optimal effect of AMF was observed at the 50% NPK dosage, which produced the best growth and yield performance, indicating that AMF application can reduce chemical fertilizer requirements without compromising crop productivity.